Crónica de una transformación anunciada (2021)
In today’s knowledge society, with the inevitable advance towards what we know as the Fourth Industrial Revolution, development approaches and theories that privilege cooperation among various significant actors for the generation, transmission and application of relevant knowledge are gaining importance. Even more so now, in the midst of this unexpected pandemic that has put us to the test as a society, has put our habits and customs to the test and, what is more relevant, has put to the test old structures, methodologies, pedagogies and didactics, forcing companies, universities, States and civil society to accelerate the inevitable transformation that had been announced in the rhetoric of our society, but that was only timidly advancing towards its realization.